2013
DOI: 10.1098/rspb.2012.2396
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-like receptors mediate pair bonding in a socially monogamous songbird

Abstract: Although many species form socially monogamous pair bonds, relevant neural mechanisms have been described for only a single species, the prairie vole (Microtus ochrogaster). In this species, pair bonding is strongly dependent upon the nonapeptides oxytocin (OT) and vasopressin, in females and males, respectively. Because monogamy has evolved many times in multiple lineages, data from additional species are required to determine whether similar peptide mechanisms modulate bonding when monogamy evolves independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 43 publications
(89 reference statements)
0
65
1
Order By: Relevance
“…For example, activation of OTRs, but not V1aRs, is necessary for the establishment of pair bonds in zebra finches, with much stronger effects in females (16,19,26). Similarly, pair bonding in female prairie voles is more strongly dependent on OTR activation than on V1aR activation, whereas the converse is true for males (27).…”
Section: Pvn Ot Neurons Promote Pair Bonding and Intrapair Affiliationmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, activation of OTRs, but not V1aRs, is necessary for the establishment of pair bonds in zebra finches, with much stronger effects in females (16,19,26). Similarly, pair bonding in female prairie voles is more strongly dependent on OTR activation than on V1aR activation, whereas the converse is true for males (27).…”
Section: Pvn Ot Neurons Promote Pair Bonding and Intrapair Affiliationmentioning
confidence: 78%
“…OTR antagonism also reduces the preference for the larger of two groups, impairs pair bonding, and reduces the preference for familiar same-sex birds. These effects are significantly stronger in females (18,19). We initially hypothesized that the antagonist effects on gregariousness and pair bonding reflect endogenous release from VP neurons in the medial bed nucleus of the stria terminalis (BSTm), given that those neurons increase their transcriptional (Fos) activity selectively in response to positive, affiliation-related stimuli (1).…”
mentioning
confidence: 99%
“…OT-like neuropeptides have played special roles in social affiliation and reproduction ever since the peptides first evolved (450 Ma), and exert widespread influences on affiliative behaviours across a variety of vertebrate classes [24]. For instance, studies have demonstrated that endogenous activation of oxytocic receptors in the brain is necessary for the natural formation of pair bonds in zebra finches [25], as has previously been shown in prairie voles [26]. An analysis of the role of OT suggests that its peripheral role is in smooth-muscle contraction, specifically in uterine contractions and lactation, and has been co-opted to serve in organizing and coordinating maternal care and motheroffspring bonding.…”
Section: (B) Why Empathy Has Evolvedmentioning
confidence: 99%
“…Moreover, yolk oestrogens, progesterone and corticosterone can also influence offspring development (Hayward and Wingfield, 2004;Groothuis et al, 2005;Gil, 2008;Henriksen et al, 2011). In this study, we hypothesize the involvement of mesotocin and vasotocin, homologues of mammalian oxytocin and vasopressin (Klatt and Goodson, 2013;Pedersen and Tomaszycki, 2012), in these prenatal effects. As the formation of bird pair bonds appears to be modulated by mesotocin and vasotocin, we reasonably suggest that our two sets of quail did not present the same levels of these nonapeptides.…”
Section: Research Articlementioning
confidence: 97%